Electron transfer via cytochrome b6f complex displays sensitivity to antimycin A upon STT7 kinase activation. Issue 1 (14th January 2022) - Buchert, Felix; Scholz, Martin; Hippler, Michael
Abstract : The cytochrome b 6 f complex ( b 6 f ) has been initially considered as the ferredoxin-plastoquinone reductase (FQR) during cyclic electron flow (CEF) with photosystem I that is inhibited by antimycin A (AA). The binding of AA to the b 6 f Qi-site is aggravated by heme- c i, which challenged the FQR function of b 6 f during CEF. Alternative models suggest that PROTON GRADIENT REGULATION5 (PGR5) is involved in a b 6 f -independent, AA-sensitive FQR. Here, we show in Chlamydomonas reinhardtii that the b 6 f is conditionally inhibited by AA in vivo and that the inhibition did not require PGR5. Instead, activation of the STT7 kinase upon anaerobic treatment induced the AA sensitivity of b 6 f which was absent from stt7-1 . However, a lock in State 2 due to persisting phosphorylation in the phosphatase double mutant pph1 ; pbcp did not increase AA sensitivity of electron transfer. The latter required a redox poise, supporting the view that state transitions and CEF are not coercively coupled. This suggests that the b 6 f -interacting kinase is required for structure-function modulation of the Qi-site under CEF favoring conditions. We propose that PGR5 and STT7 independently sustain AA-sensitive FQR activity of the b 6 f . Accordingly, PGR5-mediated electron injection into an STT7-modulated Qi-site drives a Mitchellian Q cycle in CEF conditions.